Community, individual, and referendum characteristics affecting support for conservation in Colorado - Chriestenson, Chad, author; Thilmany, Dawn, advisor; Jablonski, Becca, committee member; Weiler, Stephan, committee member (Colorado State University. Libraries, 2018)
This study investigates support for conservation amongst Colorado residents. It is pertinent given both the state's limited supply of natural resources such as water and the increasing demand for other agricultural resources such as open space along the rapidly expanding urban fringes. This is also the first such study performed in the Rocky Mountains and results indicate demand for environmental goods differs when compared to other regions in the United States. The research is performed in two distinct steps. First, revealed preferences are analyzed. These come from conservation referenda data. The analysis proceeds in an analogous manner to previous studies. The Heckman two-step process is used to determine factors affecting both appearance and passage of referenda at the county and municipal level across the state. Results indicate that larger population, higher educational attainment, home-rule charter, pre-existing support, and a lower proportion of white people all increase the likelihood of a referendum appearing on the ballot. A focus on wildlife conservation in addition to open space language within the referenda, increases the likelihood of passage, relative to simply focusing on open space. An unexpected finding is that language directing funds toward open space and conservation of agricultural resources or water decreases this likelihood. Second, stated preferences are analyzed via the results of a demographically representative survey commissioned by the Colorado Department of Agriculture. Factor analysis is utilized to determine that most responses appear to be explained by three underlying factors: the value Coloradan's place on the continued existence of agriculture in the state, a measure of views toward human's interaction with the environment, and the perceived relationship between agriculture and the environment. An ordered probit model is used to investigate how these factors, demographic variables, and survey responses affect resident's support for using public funds to help farmers conserve agricultural resources. Results indicate support for conservation decreases with age. They also suggest that those who support conservation of these resources do not appear to care about the mechanism by which they are conserved, they only care that they are conserved. Combined results from the two components of this study show younger residents with higher levels of educational attainment are more likely to support conservation. They indicate that Coloradan's stated and revealed preferences do not fully align. For instance, residents appear to support the idea of conserving water yet don't follow through in the voting booth when language including water is in a referendum. The opposite is true of wildlife conservation. Respondents appear indifferent to connecting land conservation with wildlife in their survey responses, yet referenda results suggest they are more likely to vote for such policies.